Promoting digital skills development for South African incarcerated criminal offenders - Mohohlwane, Katlego (My University, 2021)
There is a high rate of recidivism in South Africa which can largely be linked to a lack of access to formal employment and unsuccessful social reintegration following incarceration. This status-quo is, in the context of the 21st century, exacerbated by the obviation of digital skills development by the Department of Correctional Services (DCS) during the ‘rehabilitation’ of incarcerated persons. This study seeks to investigate the socioeconomic benefits that maybe realised through developing digital skills for incarcerated persons thereby promoting the need to include these in the DCS’ institutional rehabilitation programmes. To explore why digital skills should be developed within correctional facilities, a qualitative research methodology was applied for collecting, analysing and interpreting language data to identify common themes among various categories of responses and produce findings. Data was collected from a small group of respondents from the financial, retail, manufacturing, social science, and social entrepreneurship sectors and then analysed using a thematic analysis method with an inductive orientation to provide exploratory insights into the kinds of digital skills required for incarcerated persons to achieve economic entry and successful social reintegration as deemed necessary by the respondents in this research. The digital skills composition is categorised as per the Digital Skills Framework One (DSFOne) (van Greunen et al., 2015), and the conceptual framework is based on an adaptation of the New Skills Now Taxonomy (Accenture, 2017) and the Technology Acceptance Model (TAM) (Legris et al., 2003).This study finds that considering the excessive barriers to formal employment for ex-offenders, predominantly perpetuated by public perception, lack of stakeholder management on the part of the DCS, and skills development for incarcerated persons, ICT practitioner and advanced digital skills may very well be the skills category that could position previously incarcerated persons favourably for formal economic inclusion. Further, the development of digital literacy skills is materially important for the reintegration of incarcerated persons into the digital society. Lastly, the digital leadership capacity of the DCS needs to be developed to meet the requirement of effectively building digital strategies that would enable the development of requisite digital skills for incarcerated persons and leverage digital platforms to facilitate social reintegration
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business, 2021
Keywords: Incarcerated persons; criminal offenders,; digital skills development; South Africa; SDG-8: Decent work and economic growth